Clinical Evaluation of Neoadjuvant Chemotherapy Followed by Radical Hysterectomy in the Management of Cervical Cancer Stage IIB - Rizal Sanif (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To evaluate the clinical efficacy, operability, radicality, toxicity, and incidence of recurrences of neoadjuvant chemotherapy (NAC) followed by radical hysterectomy (RH) among patients with stage IIB cervical cancer. Method: This is an observational clinical study at Dr. Moh. Hoesin Hospital, Palembang. Data were analyzed from 27 patients who matched the inclusion criteria and underwent 3 cycles of neoadjuvant chemotherapy (NAC) with Paclitaxel (75 mg/m2) in combination with Cisplatin (50 mg/m2) and Docetaxel (75 mg/m2) combined with Carboplatin (300 mg/m2) according to AUC 6, followed by radical hysterectomy from January 2012 until December 2013. Result: The operability rate after NAC was 96.4%. Lymph node metastases were negative in 75% of patients, and we found bilateral lymph node metastases in 14.3% of patients. Parametric infiltrations were negative in 85.7% of the patients, and positive in 14.3% of patients. No vaginal infiltrations were found. As much as 89.3% of the patients did not experience any side effect, while anemia and thrombocytopenia were found in 10.8% of the patients. We found that 7.1% of patients had recurrences within 6 months interval. Conclusion: NAC followed by radical hysterectomy showed significant advantages for patients with stage IIB cervical cancer, with fewer side effects. However, long-term evaluation and a larger number of patients are required to confirm this result. Keywords: cervical cancer, neoadjuvant chemotherapy, radical hysterectomy